Did My Hand Move in a Mirror? Body Ownership Induced by the Mirror Hand Illusion - Iida, Akihiro; Saito, Hidekazu; Ota, Hisaaki (Frontiers in Human Neuroscience, 2021)
Although the induction of body ownership illusion on mirror images is well known, the effect of concomitant tactile stimulation remains unknown. Therefore, we investigated how synchronous or asynchronous tactile stimulus on mirror images affects the induction of body ownership illusion. Fifteen right-handed healthy participants (mean age 22.9 ± 1.0 years) were enrolled in the study. The participants experienced illusory body ownership through tactile stimulations that were either synchronized or unsynchronized with the mirror image. Proprioceptive drift and illusory shift of the felt position of the real hand toward the mirrored hand were used for quantitative evaluation of body ownership and were measured at “baseline,” “immediately after stimulation,” “two minutes after stimulation,” and “four minutes after stimulation”. The qualitative degree of body ownership was evaluated by a questionnaire. We found that proprioceptive drift occurred from immediately after to four minutes after stimulation in both stimulation conditions. The results of the questionnaire revealed that body ownership rating was higher in the synchronous condition than in the asynchronous condition. This may be attributed to the combination of quantitative and qualitative body ownership induction in the synchronous condition, rendering it superior to the asynchronous condition. Our results may contribute to the understanding of the multisensory integration mechanism of visual and tactile stimulation during mirror illusion induction.